2018
DOI: 10.1088/1361-6382/aab06a
|View full text |Cite
|
Sign up to set email alerts
|

Generalized wave operators, weighted Killing fields, and perturbations of higher dimensional spacetimes

Abstract: We present weighted covariant derivatives and wave operators for perturbations of certain algebraically special Einstein spacetimes in arbitrary dimensions, under which the Teukolsky and related equations become weighted wave equations. We show that the higher dimensional generalization of the principal null directions are weighted conformal Killing vectors with respect to the modified covariant derivative. We also introduce a modified Laplace-de Rham-like operator acting on tensor-valued differential forms, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Finally, we mention that the generalized Teukolsky connection and the closely related 'weighted Killing fields' found in [3] for perturbations of higher dimensional spacetimes, can be shown to follow the same principle as the one exploited here, namely conformal and GHP covariance. However, the question about conformal invariance of field equations in higher dimensions is much more subtle than in the 4-dimensional case (in particular, Maxwell fields in d = 4 are not conformally invariant).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Finally, we mention that the generalized Teukolsky connection and the closely related 'weighted Killing fields' found in [3] for perturbations of higher dimensional spacetimes, can be shown to follow the same principle as the one exploited here, namely conformal and GHP covariance. However, the question about conformal invariance of field equations in higher dimensions is much more subtle than in the 4-dimensional case (in particular, Maxwell fields in d = 4 are not conformally invariant).…”
Section: Discussionsupporting
confidence: 57%
“…(1.6) Interestingly enough, it was found in [3] that (1.6) solves the equation 7) and therefore it can be considered as a Killing spinor with respect to the Teukolsky connection (in [3] these objects were called 'weighted' Killing spinors). The ordinary Killing spinor K AB = Ψ −1/3 2 o (A ι B) of type D spacetimes mentioned above is just a particular case of (1.6)-(1.7).…”
Section: Introductionmentioning
confidence: 99%
“…This form of the gauge potentials was pointed out in [15,16], where Araneda derived the form of gauge potential on a type-D vacuum spacetime with cosmological constant. Our result generalizes it to non-vacuum case.…”
Section: Gauge Potentials Of Maxwell Fieldmentioning
confidence: 74%
“…For s = ±2, even in four dimensions, the separation of variables in the linearised Einstein equation has not been realized so far except in the vacuum case. It is remarkable that Araneda [15,16]…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The separation of variables in higher-dimensional Maxwell equations remained an open problem for a long time. A partial success was achieved in [24] where it was demonstrated that such equations can be decoupled, using the higher-dimensional generalization of the Newman-Penrose formalism [25], provided that the background spacetime is Kundt, i.e., it admits a null geodesic congruence which is all: shear-free, twist-free, and expansion-free. Unfortunately, the higher-dimensional rotating black hole spacetimes do not belong to this class.…”
Section: Introductionmentioning
confidence: 99%